Identificação, caracterização e validação de sequências microssatélites no genoma do mico-leão-preto (Leontopithecus chrysopygus) - Pardo, Priscilla Pina (Universidade Federal de São Carlos, 2015)
The black lion tamarin (Leontopithecus chrysopygus) is one of the most endangered neotropical primates and the historical causes that led them to the brink of extinction are closely related to the history of the Atlantic Rainforest. Among its main threats are the fragmentation of their habitat, the small number of his surviving populations and the isolation of them, which directly affect the genetic structure of these populations. The use of genetic analysis and molecular markers for the wildlife conservation have been growing over the past few years with the advent of genetic and molecular technologies and bioinformatics, allowing the establishment of rapid diagnosis of diseases and many genetic and ecological parameters such as migration rate, population size, genetic diversity, kinship relations. Among the main molecular markers are microsatellite that consist of short DNA sequences tandemly repeated composed of 1 to 6 bases pairs widely distributed in eukaryotic and prokaryotic genomes. Characteristics like codominance and high level of polymorphism make microsatellites an important tool to measure the loss of genetic diversity and recent changes in genetic structure of populations, and for use in forensic investigations. Among the methods used for the isolation of such markers, is the in silico mining for species with available genetic data. In the present study, we identified 60 tetranucleotide microsatellite loci have been identified in the genome of common marmoset (Callithrix jacchus) through data mining conducted in the genome of this species. Primer pairs were designed and tested in black lion tamarin, since this kind does not have any genomic data available. Of the 60 loci tested, 87% had successful amplification of DNA samples from 10 captive animals. PCR products were analyzed on agarose gel and 13 loci were genotyped in automatic sequencer ABI3730XL. The Geneious version 8.1.6 software was used for genotyping. Only four loci showed polymorphism, observed two alleles per locus. This low polymorphism may be associated with the origin of the captive colonies.
Keywords: Leontopithecus chrysopygus; Marcadores Moleculares; Microssatélites; Data Mining; Amplificação Heteróloga; Anotação Genômica; Leontopithecus chrysopygus; Molecular Markers; Microsatellites; Data Mining; Cross-species amplification; Genome Annotation; CIENCIAS BIOLOGICAS